2022
DOI: 10.1186/s40658-022-00514-7
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing spatial distribution between 18F-fluorodeoxyglucose and 18F-boronophenylalanine positron emission tomography to investigate selection indicators for boron neutron capture therapy

Abstract: Background 18F-FDG PET is often utilized to determine BNCT selection due to the limited availability of 18F-BPA PET, which is performed by synthesizing 18F into the boron drug used for BNCT, although the uptake mechanisms between those are different. Additionally, only a few non-spatial point parameters, such as maximum SUV (SUVmax), have reported a correlation between those in previous studies. This study aimed to investigate the spatial accumulation pattern between those PET images in tumors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
(121 reference statements)
0
4
0
Order By: Relevance
“…reported that the SUV max /SUV of normal tissue (SUV N ), mean SUV, SUV min , and Vo2.5 (tumor volume ratio of SUV max /SUV N ≥ 2.5) were not prognostic factors for complete response rate. In their study, SUV min /SUV N was the only significant factor; however, SUV min and SUV N are difficult to use as indicators because they are less reproducible owing to their small range of values and their dependence on how the ROI is set 22 . By contrast, a previous study reported that increased LAT1 expression also increased the uptake capacity of BPA by tumors 29 .…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…reported that the SUV max /SUV of normal tissue (SUV N ), mean SUV, SUV min , and Vo2.5 (tumor volume ratio of SUV max /SUV N ≥ 2.5) were not prognostic factors for complete response rate. In their study, SUV min /SUV N was the only significant factor; however, SUV min and SUV N are difficult to use as indicators because they are less reproducible owing to their small range of values and their dependence on how the ROI is set 22 . By contrast, a previous study reported that increased LAT1 expression also increased the uptake capacity of BPA by tumors 29 .…”
Section: Discussionmentioning
confidence: 82%
“…In their study, SUV min /SUV N was the only significant factor; however, SUV min and SUV N are difficult to use as indicators because they are less reproducible owing to their small range of values and their dependence on how the ROI is set. 22 By contrast, a previous study reported that increased LAT1 expression also increased the uptake capacity of BPA by tumors. 29 Onishi et al 30 reported that the overexpression of LAT1 in cancer cells enhanced the therapeutic effect of BNCT in vitro.…”
Section: T a B L Ementioning
confidence: 79%
See 1 more Smart Citation
“…However, there are limited data on the uptake of amino acid PET in untreated brain metastases, and uptake may vary depending on the tumor type. Recent research has demonstrated promising results, particularly indicating that 18 F-FBPA PET with computed tomography (CT) surpasses 18 F-fluorodeoxyglucose ( 18 F-FDG) PET/CT in the differential diagnosis of malignant tumors and benign lesions [144,145]. These findings strongly suggest that employing 18 F-FBPA PET/CT may significantly reduce the occurrence of false-positive diagnoses when compared to 18 F-FDG PET/CT.…”
Section: Future Directionsmentioning
confidence: 99%